2006
DOI: 10.1007/s11104-005-4725-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Different Mechanisms to Zinc Efficiency in Bread Wheat During Early Vegetative Stage

Abstract: Zinc (Zn) has a vast number of functions in plant metabolism and consequently Zn deficiency has a range of effects on plant growth. There are a number of different possible mechanisms by which plants tolerate Zn deficiency (generally expressed as Zn efficiency), such as Zn uptake, translocation to the shoot and physiological efficiency. However, there have been no direct comparisons of the relative importance of these possible mechanisms of Zn efficiency in a large set of genotypes of contrasting Zn efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 34 publications
5
44
0
Order By: Relevance
“…Previous screening of bread wheat genotypes at a range of soil Zn levels showed this pair had the largest difference in Zn efficiency (Genc et al 2006). The DH population was increased in University of California soil mix (Barker et al 1998) in the glasshouse to minimize variation in grain Zn content within the population since high seed Zn content can significantly affect growth under Zn-deficient conditions (Rengel and Graham 1995;Yilmaz et al 1998;Genc et al 2000).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous screening of bread wheat genotypes at a range of soil Zn levels showed this pair had the largest difference in Zn efficiency (Genc et al 2006). The DH population was increased in University of California soil mix (Barker et al 1998) in the glasshouse to minimize variation in grain Zn content within the population since high seed Zn content can significantly affect growth under Zn-deficient conditions (Rengel and Graham 1995;Yilmaz et al 1998;Genc et al 2000).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Although these studies have demonstrated considerable genetic variation and improved our understanding of the physiological mechanisms responsible for tolerance, no varieties of any cereal species have been bred specifically for this trait. The lack of success has been because firstly, screening methods are generally labour-intensive and slow, and in field trials show a large environmental influence, and secondly the Zn efficiency in cereals is a physiologically complex trait (Rengel 1999;Gao et al 2005;Genc et al 2006). There has been little work to characterise the genetic basis of Zn efficiency in wheat, but an analysis of the Opata x Synthetic bread wheat mapping population showed continuous variation in Zn efficiency suggesting that it is a quantitative trait and polygenic (Y.…”
mentioning
confidence: 99%
“…Alth Zinc (Zn) is an essential element for higher plants, and its importance in agriculture is increasingly being recognized (Genc et al, 2006). Low Zn availability in soil is common worldwide, and Zn deficiency leads to reductions in crop yield (Cakmak et al, 1996;Rengel and Graham, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The grain Zn concentration of a genotype reflects its ability to take up Zn from the soil, to mobilize Zn from different parts of the plant and to load it in the grain (Pearson et al 1995;Genc et al 2006). It is desirable to combine the ability to load Zn into the grain with a high yield potential.…”
Section: Introductionmentioning
confidence: 99%